A Balancing Act between Anniversary Publication and Scientific Study (KULT_online, 2020)
In July 2019 the Berlin Zoological Garden celebrated its 175th anniversary. Historian Clemens Maier-Wolthausen was commissioned to write the eventful history of the oldest German zoo from its beginnings in the 1840s to the recent past. The work is not only an anniversary publication, but also aims to be a historiographical treatise and is particularly concerned with reappraising the zoo's National Socialist past. The book fulfills this claim – apart from a few short-comings.